OSTEOSSARCOMA: DEFINIÇÃO, INCIDÊNCIA E TRATAMENTOS DA DOENÇA - Gregolon, Bruna; Antunes, Rafaela; Bernardo, Ana Maressa; Schneider, Taiane; Cezario, Kamila Cerbaro; Fraporti, Liziara (Anais de Saúde Coletiva; v. 2 n. 2 (2022): 2022/2, 2023)
Sarcoma Osteogênico. Osteossarcoma. Antineoplásicos.